Developing Problem-Based Inquiry Model in Indonesian Learning in General High Schools - Ikawati, Erna; Pohan, Jusrin (Journal of Languages and Language Teaching, 2023)
This research is motivated by the importance of collaboration between teachers and students in learning Indonesian. This collaboration is marked by cooperation in improving the quality of learning by designing inquiry-based Indonesian language learning model books. This model book is designed to be more attractive to educators and students by considering the content and design to suit the needs and characteristics of students. This research aims to develop an inquiry-based Indonesian language learning model that is viewed from the aspects of validity, practicality and effectiveness. The research uses research and development methods using the Plomp model which consists of preliminary research, prototypes and assessment. Research findings reveal that the model developed produces high validity seen from the results of expert assessments, while the practicality of the model shows very high results seen from teacher assessments when testing this model. Apart from that, the effectiveness of the model is very effective as seen from the presentation of this model which is clear and well organized, the language used is easy to understand, and the structure of the model is attractive. Overall, this model can be applied well in Indonesian language learning, because it can improve student learning outcomes.